Studi Hermeneutik-Filosofis Teks Lelaku Tapa Wuda Ratu Kalinyamat sebagai Simbol Pendidikan Agama Islam - Muhammad Rifqi Zam Zami; Nur Widad Mazaya; Widia Astuti (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
This article discusses about the hidden meaning of tapa wuda that had performed by Kalinyamat Queen as a symbol of Islamic education. This ritualistic behavior recorded in the Babad Tanah Jawi text which is often invites controversy about its meanings. Many people interpret tapa wuda textually as